The Significance of School Digitalization in Elementary Education: Empirical Evidence from Regression Analysis - Ahmad Jubaidi; Tina Rahmawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
School digitalization integrates technology into education to enhance learning quality. However, limited teacher skills in utilizing learning technology and insufficient ICT-based media pose challenges. This study examines the effect of school digitalization on elementary education quality using a quantitative method with 37 respondents from UPT SDN 01 Bukit Gemuruh, UPT SDN 01 Sumamukti, and UPT SDN 01 Bumi Dana. Data were collected through questionnaires and observations, analyzed using simple regression and T-tests. Results show a positive and significant impact, with a Sig. value of 0.012 ≤ 0.05 and tcalculated (2.653) ≥ ttable (2.030). The coefficient of determination is 16.7%, indicating school digitalization's role, though its influence is moderate. Efforts to address challenges include teacher ICT training and funding for digital learning media. These findings provide insights for teachers, principals, and policymakers to optimize school digitalization for better education quality.